Odontotrypes (Odontotrupes) tawangensis new species (Coleoptera: Geotrupidae) from Arunachal Pradesh, India - Gupta, Devanshu; Chandra, Kailash; Hillert, Oliver (Zootaxa, 2016)
A new species of the genus Odontotrypes Fairmaire, 1887 (Coleoptera: Geotrupidae) belonging to the subgenus Odontotrupes Boucomont, 1905 is described from the Tawang district, State of Arunachal Pradesh (northeast India): Odontotrypes (Odontotrupes) tawangensis new species. Relevant diagnostic characters (pronotum, head, elytra, profemur, scutellar shield, and external male genitalia) are illustrated and compared with closely related species of this subgenus, in particular Odontotrypes (Odontotrupes) orichalceus (Fairmaire, 1895). The distribution of the new species is mapped.